Optimising the First Year Experience in Law: The Law Peer Tutor Program at the University of New South Wales - Dominic Fitzsimmons; Simon Kozlina; Prune Vines (Legal Education Review)
Because alternative dispute resolution processes are entrenched in the Australian legal system, alternative dispute resolution courses are included in most law school curricula Australia-wide. The article examines the origins and status quo of alternative dispute resolution legal education. The article also considers whether the adversarial, lawyer-centred elements of the current legal culture are capable of being transformed into a more collaborative, client centred approach to practising law.